2017
DOI: 10.1080/14712598.2017.1347630
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus (AAV) gene therapy for cystic fibrosis: current barriers and recent developments

Abstract: Introduction Since the CF gene was discovered in 1989, researchers have worked to develop a gene therapy. One of the most promising and enduring vectors is AAV, which has been shown to be safe. In particular, several clinical trials have been conducted with AAV serotype 2. All of them detected viral genomes, but identification of mRNA transduction was not consistent; clinical outcomes in Phase II studies were also inconsistent. The lack of a positive outcome has been attributed to a less-than-efficient viral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 72 publications
0
34
0
2
Order By: Relevance
“…23,86,[89][90][91][92][93] Although adeno-associated viral delivery of CFTR cDNA has been well tolerated and shown to partially restore CFTR function, the resulting expression of CFTR cDNA is weak, with diminishing efficacy on repeat exposure. [94][95][96][97] One recent phase 2b trial delivered CFTR DNA using a liposomal delivery system (GL67A/pGM169) demonstrated that, after repeat nebulization monthly for 1 year, treatment groups of cystic fibrosis patients exhibited stabilized lung function, whereas the placebo group experienced a decline. 98 Notably, only 30% of patients showed a response in NPD following CFTR stimulation, with a maximum of À7.0 mV.…”
Section: Discussionmentioning
confidence: 99%
“…23,86,[89][90][91][92][93] Although adeno-associated viral delivery of CFTR cDNA has been well tolerated and shown to partially restore CFTR function, the resulting expression of CFTR cDNA is weak, with diminishing efficacy on repeat exposure. [94][95][96][97] One recent phase 2b trial delivered CFTR DNA using a liposomal delivery system (GL67A/pGM169) demonstrated that, after repeat nebulization monthly for 1 year, treatment groups of cystic fibrosis patients exhibited stabilized lung function, whereas the placebo group experienced a decline. 98 Notably, only 30% of patients showed a response in NPD following CFTR stimulation, with a maximum of À7.0 mV.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] However, the levels of expression in patients with cystic fibrosis (CF) enrolled in the first clinical trial were found to be generally low. 18,20,21 Further studies have shown that targeted deletions in the CFTR CDS, to allow inclusion in the AAV genome of longer and more efficient promoters and/or enhancers, result in higher efficiency of CFTR reconstitution in cells, 9,14,15,[22][23][24] confirming that reducing the length of the expression cassette by minimizing the size of the regulatory elements, at the cost of their strength, might limit the efficacy of the gene therapy approach.…”
Section: Fitting Large Genes In a Single Aav Vectormentioning
confidence: 99%
“…The large size of the CFTR CDS (*4.4 kb), indeed, leaves little space for the regulatory elements in the vector; therefore, a number of efforts have been directed toward shrinking the CFTR expression cassette by either generating truncated forms of CFTR that retain their functionality or identifying short promoter/polyA signals. 15 Flotte et al first attempted the delivery of an AAV vector in which the expression of a truncated version of CFTR was driven by the ITRs of AAV. These, indeed, were found to have a low promotorial activity, resulting in detectable levels of CFTR both in vitro and in vivo.…”
Section: Fitting Large Genes In a Single Aav Vectormentioning
confidence: 99%
“…One of the possible reasons of these discouraging results may be attributed to the limited packaging of AAV, resulting in a low expression of the CFTR cDNA. Although AAVs present some disadvantages, arising mainly from the use of viruses as carriers, the ongoing research is trying to address and improve these limitations and develop novel and safer formulations (Griesenbach and Alton, 2012;Guggino and Cebotaru, 2017).…”
Section: Viral Vectorsmentioning
confidence: 99%